(untitled) (Singapore, 1991)
This volume gathers the written contributions of the courses and lectures given during the session on combustion modelling, which was held in INRIA in Rocquencourt (France) in March 1989.
Keywords: Combustion,Đốt cháy; Mathematical models,Mô hình toán học